Optimalisasi Penggunaan Nitrogen pada Tanaman Jagung di Tanah Marginal Melalui Bakteri Penambat Nitrogen dan Limbah Udang - Pudjiwati, Eko Hary; Damanik, Desy Kurnia (Journal Galung Tropika, 2025)
Marginal land has low productivity due to its limited soil fertility, especially in terms of nitrogen (N) availability. The use of nitrogen-fixing bacteria and shrimp waste as alternative organic fertilizers can increase nitrogen use efficiency in sweet corn (Zea mays saccharata), which is an important food commodity. This study aims to determine the ability of nitrogen-fixing bacterial isolates to increase N nutrient use and their effect on the growth and production of sweet corn when applied together with shrimp waste. This study was conducted using a randomized block design (RAK) with a treatment of 20 tons/ha of shrimp waste and chemical fertilizer (50% Urea + 100% SP-36 + 100% KCl) with the addition of nitrogen-fixing bacterial isolates, consisting of 5 treatments and 4 replicates, namely no fertilizer, shrimp waste, and nitrogen-fixing bacteria. Other treatments were control, which was 100% Urea + 100% KCL + 100% SP-36; then isolate BPN1; isolate BPN2; isolate BPN3. The results of the study show that the application of nitrogen-fixing bacteria and shrimp waste technology packages can increase soil organic carbon content, nitrogen nutrient uptake, nitrogen nutrient uptake efficiency, and agronomic efficiency of sweet corn crops on marginal land. In addition, this technology can also reduce urea fertilizer use by up to 50%. This technology has the potential to be an environmentally friendly solution to support sustainable agriculture on marginal land.